Maus-tratos contra a pessoa idosa - da suspeita à notificação: um desafio para os profissionais do Hospital do Servidor Público Municipal - Jardim, Sueli Erasma Gaspar (2010)
The present study aims to investigate, within the elderly patients in inpatient units of the Hospital do Servidor Público Municipal HSPM (State Civil Servants Hospital), those suspected of being victims of maltreatments. The sample includes forty-eight (48) patients whose cases were submitted to the Special Action Group for Elderly Protection (GAEPO) between January, 2006 and December, 2008. Document research technique was utilized for data collection, against analysis of the medical records and the social study cards of these patients. Patients were characterized according to social-demographic variables, family conditions, hospitalization and suspect of maltreatment. An evaluation of the sample indicates that women are predominant (62.50%) and concentrated in the age group between 80 and 89 being this range a little lower for men, who stay between 70 and 79 years. Both genders had little education and low income. Neglect and abandonment were the main types of suspected violence committed. Reasons for admission were much varied, with predominance of dementia syndrome diagnosis, a fact rendering difficult the confirmation of occurrence of maltreatment. Only one aged patient did not present a pattern of dependence and more than one half was hospitalized for intervals longer than a month. The evolution, in most cases, consisted in transfer to other institutions better qualified to take care of aged patients. The objective of this study is to provide inputs to the team, for identification of signs of suspected abuse against the elderly in treatment at HSPM and thus contribute to the consolidation of denounces to the competent judicial bodies